Perfil dos participantes do núcleo UNESP-UNATI do campus de Presidente Prudente - Converso, Maria Estelita Rojas [UNESP] (2005)
Because of the great increase of the senior population in all world, a larger concern exists in turning the most productive and healthy old age. With this purpose, the Núcleo UNESP-UNATI of the campus of Presidente Prudente, tries to contribute offering several activities and providing an important social integration among these individuals. Like this, is necessary to characterize them and to know their interests better for refine and a planning of the activities, doing with that these assist the expectations and needs of the participant group. For the characterization data were collected on sex, education, marital status and home. It is noticed, for the results, that most of the participants lives with their relatives in detriments of the ones that live alone. In relation to the marital status the married ones prevail. In agreement with the education degree, we had a high index of participants with higher education, starting from 2002, that just in the year of 2001 it was crossed by a larger index of participants with incomplete fundamental teaching, fact that can also be explained by the type of activities that were inserted in the program. The predominant age group was of 50 and 70 years for both sexes. In agreement with the obtained results, we can notice that the senior this being moved as active agent of their own health, always looking for to improve their quality of life.